The Impact of Vitamin C Supplementation on Recovery from Diabetes-Induced Alterations on Lipid Structure and Function of Rat Testis: An FTIR Imaging Study - Ustaoglu, Sebnem Garip; Tas, Damla Guldag; Yilmaz, Okkes; Severcan, Feride (Asia Pacific Acad Science Pte. Ltd., 2023)
Background: As a main micronutrient, Vitamin C is crucial for preserving the body's homeostasis and regular metabolic functions. The goal of this study is to evaluate the impact of Vitamin C on diabetes-induced changes in the lipid content, conformation/structure and dynamics of testicular tissue using Fourier Transform Infrared (FTIR) microspectroscopic technique.Methods: Male Wistar rats were classified into 4 as: control, diabetic, low (15 mg/kg/day) and high (100 mg/kg/day) Vitamin C-treated groups. The animals in the diabetic and treated groups were first given Streptozotocin (STZ). Diabetic animals were chosen according to their blood glucose levels (values equal to or higher than 300 mg/dL). Vitamin C therapy was started 7 days after STZ treatment and continued for 5 weeks, after which the testis tissues were removed and used for FTIR microspectroscopy studies. The spectral parameters that were evaluated included relative saturated and unsaturated lipid contents, unsaturation indices, lipid orders/disorders and membrane fluidity values.Results: There was a significant reduction in saturation levels, lipid acyl chain length, lipid dynamics (p < 0.001 for all of the mentioned parameters), in addition to an increase in unsaturation levels (p < 0.001) as a result of lipid peroxidation and higher lipid order (p < 0.01) in diabetic tissues, compared to the control rat group. Those variations were significantly recovered by an increase in saturated lipid amount, lipid acyl chain length and dynamics (p < 0.01) with a decrease in unsaturated lipid content (p < 0.001) and lipid order (p < 0.01) in the testis of the low dosage of Vitamin C therapy group compared to the diabetic group. Those parameters were taken to close values to the control group by the low dosage of Vitamin C therapy. Even though high dosage of Vitamin C was also successful in enabling recovery from most of the effects of diabetes on the tissue (p < 0.05 for lipid order,p < 0.01 for saturation andp < 0.001 for unsaturation index), it could not overcome the diabetic effects on the membrane dynamics of the testis tissue.Conclusions: Low dosages of Vitamin C can repair the diabetes-induced damage efficiently and protect the cells and the biomembranes against the damage originating from lipid peroxidation in the tissues.
Keywords: Vitamin C; FTIR imaging; FTIR microspectroscopy; diabetes; lipid peroxidation